A comparison between continuous indirect calorimetry and single weight-based formula in estimating resting energy expenditure in nutritional therapy: a prospective randomized controlled study in critically ill patients - Farah Hanim A; Cheah, Saw Kian; Nadia Md Nor; Rufinah Teo; Wan Rahiza Wan Mat (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Optimal nutritional therapy is important to improve outcome in critically ill population in an intensive care unit (ICU). Although indirect calorimetry (IC) is currently a gold standard for resting energy expenditure (REE) measurement, yet it is still not routinely used in the ICU. A total of 146 mechanically ventilated patients were randomised to receive enteral nutrition (EN) with energy targeted based on continuous indirect calorimetry (IC) measurements (IC group, n=73) or according to 25 kcal/kg/day (SWB group, n=73). Patient characteristics were equally distributed and the IC group showed lower mean measured REE (1668.1 + 231.7 vs 1512.0 + 177.1 kcal, p<0.001). Results also showed a significant deficiency in the daily (-148.8 + 105.1 vs. -4.99 + 44.0 kcal, p<0.001) and total cumulative energy balances (-1165.3 + 958.1 vs. 46.5 + 369.5 kcal, p<0.001) in the SWB group as compared to the IC group. From the Kaplan-Meier survival analysis, we found that ICU mortality was significantly lower in the IC group with better survival probability compared to the SWB group (log-rank test, p = 0.03). However, both groups showed comparable results in terms of ICU length of stay, duration of mechanical ventilation and incidence of feeding intolerance. In conclusion, this study showed that tightly supervised nutritional therapy based on continuous IC measurement provides significantly less mean daily and cumulative energy deficits as well as significantly reduced ICU mortality rate.